Ferromagnetism in ultrathin MoS2 nanosheets: from amorphous to crystalline - Zhang, Rongfang (Springer, 2014)
Two-dimensional materials have various applications in the next generation nanodevices because of their easy fabrication and particular properties. In this work, we studied the effects of crystalline order on the magnetic properties of ultrathin MoS2 nanosheets. Results indicate that all the fabricated samples show clear room temperature ferromagnetism. The amorphous sample has the larger saturation magnetization than that of the crystallized samples, where the disordered grain boundary or defects in the nanosheets are considered to be responsible for the long-range magnetic order. These MoS2 nanosheets with versatile functions may have potential applications in spintronics, nanodevices, and photodevices.